Quantum disc plus inverse square potential. An analytical model for two-dimensional quantum rings: Study of nonlinear optical properties (2012)
ABSTRACT: The exact solutions for the two‐dimensional motion of a conduction band electron in a disc shaped quantum dot under the effect of an external magnetic field and parabolic and inverse square confining potentials are used to calculate the linear and nonlinear optical absorption as well as the linear and nonlinear corrections to the refractive index in the system. It is shown that this kind of structure may work well as a model for a quantum ring. Using the basic parameters typical of the GaAs, the results show that the influence of the normally oriented magnetic field induces a blueshift in both the first and third order peaks of the calculated optical quantities. In addition, total peak amplitudes are shown to be growing functions of the magnetic field strength. The increase in the strength of the inverse square potential function enhances significantly the contribution from the nonlinear third‐order terms in both the absorption and the relative correction to the refractive index.